Recognition of Human Activities via Wearable Sensors - Variables Identified in a Systematic Mapping - Nardin, Luciana De; Rodrigues, Kamila R. H.; Zimmermann, Larissa C.; Orlandi, Brunela D. M.; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2020: Proceedings of the 26th Brazilian Symposium on Multimedia and the Web, 2020)
Worldwide, the composition of the population registers an increase in life expectancy and a reduction in the birth rate. The creative use of technology and the omnipresence of sensor-based devices allow the development of software solutions and platforms that offer services to older people towards increasing quality of life, reducing expenses, and promoting aging in place while preserving autonomy and security: a case in point is wearable sensor-based Human Activity Recognition (HAR). Given that previous work observed the lack of attention given to older people by the researchers investigating HAR systems, we conducted a systematic mapping aiming at identifying resources, as variables and associated values, used in the development of HAR systems for older people. The systematic mapping selected 21 papers published between 2010 and 2019, which exposed the use of 16 variables and associated values.